Multi-dimensional roles of sodium-glucose cotransporter 2 inhibitors: beyond hypoglycemic and cardiorenal protection - Li, Siyu; Wang, Yaqi; Gong, Quan (Frontiers in Endocrinology, 2025)
Sodium glucose cotransporter-2 inhibitors (SGLT2i) have been found to have a range of benefits, including improving obesity and insulin resistance, hyperuricemia, hypertension, hyperlipidemia, and other metabolic disorders. Initially used for the hypoglycemic effects, they are now found to benefit atherosclerotic cardiovascular disease and chronic kidney disease. Additionally, SGLT2i has been found to have multiple functions, such as improving liver metabolism, affecting brain function, protecting islet β cell function, anti-tumor, and affecting immune system function. This review provides an overview of the protective effects of SGLT2i on different organs and tissues, as well as the potential mechanisms underlying the functional improvement induced by SGLT2i in recent years.